ANALYSIS OF LONG-TERM BACTERIAL VS. CHEMICAL FE(III) OXIDE REDUCTION KINETICS - Roden E.E. (My University, 2004)
Data from studies of dissimilatory bacterial (108 cells mL−1 of Shewanella putrefaciens strain CN32, pH 6.8) and ascorbate (10 mM, pH 3.0) reduction of two synthetic Fe(III) oxide coated sands and three natural Fe(III) oxide-bearing subsurface materials (all at ca. 10 mmol Fe(III) L−1) were analyzed in relation to a generalized rate law for mineral dissolution (Jt/m0 = k′(m/m0)γ, where Jt is the rate of dissolution and/or reduction at time t, m0 is the initial mass of oxide, and m/m0 is the unreduced or undissolved mineral fraction) in order to evaluate changes in the apparent reactivity of Fe(III) oxides during long-term biological vs. chemical reduction. The natural Fe(III) oxide assemblages demonstrated larger changes in reactivity (higher γ values in the generalized rate law) compared to the synthetic oxides during long-term abiotic reductive dissolution. No such relationship was evident in the bacterial reduction experiments, in which temporal changes in the apparent reactivity of the natural and synthetic oxides were far greater (5–10 fold higher γ values) than in the abiotic reduction experiments. Kinetic and thermodynamic considerations indicated that neither the abundance of electron donor (lactate) nor the accumulation of aqueous end-products of oxide reduction (Fe(II), acetate, dissolved inorganic carbon) are likely to have posed significant limitations on the long-term kinetics of oxide reduction. Rather, accumulation of biogenic Fe(II) on residual oxide surfaces appeared to play a dominant role in governing the long-term kinetics of bacterial crystalline Fe(III) oxide reduction. The experimental findings together with numerical simulations support a conceptual model of bacterial Fe(III) oxide reduction kinetics that differs fundamentally from established models of abiotic Fe(III) oxide reductive dissolution, and indicate that information on Fe(III) oxide reactivity gained through abiotic reductive dissolution techniques cannot be used to predict long-term patterns of reactivity toward enzymatic reduction at circumneutral pH.